Small intestine lamina propria dendritic cells promote de novo generation of Foxp3 T reg cells via retinoic acid - Sun, Cheng-Ming (The Rockefeller University Press, 2007)
To maintain immune homeostasis, the intestinal immune system has evolved redundant regulatory strategies. In this regard, the gut is home to a large number of regulatory T (T reg) cells, including the Foxp3(+) T reg cell. Therefore, we hypothesized that the gut environment preferentially supports extrathymic T reg cell development. We show that peripheral conversion of CD4(+) T cells to T reg cells occurs primarily in gut-associated lymphoid tissue (GALT) after oral exposure to antigen and in a lymphopenic environment. Dendritic cells (DCs) purified from the lamina propria (Lp; LpDCs) of the small intestine were found to promote a high level of T reg cell conversion relative to lymphoid organ–derived DCs. This enhanced conversion by LpDCs was dependent on TGF-β and retinoic acid (RA), which is a vitamin A metabolite highly expressed in GALT. Together, these data demonstrate that the intestinal immune system has evolved a self-contained strategy to promote T reg cell neoconversion.